Lysophosphatidic Acid and Glutamatergic Transmission - Roza, Carolina; Campos-Sandoval, José A.; Gómez-García, María C.; Peñalver, Ana; Márquez, Javier (Frontiers in Molecular Neuroscience, 2019)
Signaling through bioactive lipids regulates nervous system development and functions. Lysophosphatidic acid (LPA), a membrane-derived lipid mediator particularly enriched in brain, is able to induce many responses in neurons and glial cells by affecting key processes like synaptic plasticity, neurogenesis, differentiation and proliferation. Early studies noted sustained elevations of neuronal intracellular calcium, a primary response to LPA exposure, suggesting functional modifications of NMDA and AMPA glutamate receptors. However, the crosstalk between LPA signaling and glutamatergic transmission has only recently been shown. Stimulation of presynaptic LPA receptors in hippocampal neurons regulates glutamate release from the presynaptic terminal, while excess of LPA signaling results in overexcitation and hippocampal epilepsy. Further evidences indicating a role of LPA in the modulation of neuronal transmission has been inferred from animal models with deficits on LPA receptors, mainly LPA1 which is the most prevalent receptor in human and mouse brain tissue. LPA1 null-mice exhibit cognitive and attention deficits characteristic of schizophrenia which are related with altered glutamatergic transmission and reduced neuropathic pain. Furthermore, silencing of LPA1 receptor in mice induced a severe down-regulation of the main glutaminase isoform (GLS) in cerebral cortex and hippocampus, along with a parallel sharp decrease on active matrix-metalloproteinase 9. The downregulation of both enzymes correlated with an altered morphology of glutamatergic pyramidal cells dendritic spines towards a less mature phenotype, indicating important implications of LPA in synaptic excitatory plasticity which may contribute to the cognitive and memory deficits shown by LPA1-deficient mice. In this review, we present an updated account of current evidences pointing to important implications of LPA in the modulation of synaptic excitatory transmission.